(untitled) (Contemporary Issues in Social Sciences and Management Practices, 2024)
This study investigates the effects of financial leverage, market share, and dividend policy on firm value within the global technology sector. Using data from 120 publicly listed technology companies over the period from 2010 to 2022, a multiple regression analysis is employed to examine how these independent variables influence firm value, as measured by market capitalization. The findings show that financial leverage negatively impacts firm value, as higher debt levels increase financial risk and reduce investor confidence. Market share demonstrates a strong positive effect, with companies holding larger market shares benefiting from economies of scale and competitive advantages, leading to higher valuations. Moreover, dividend policy is found to play a significant role in influencing firm value. Firms with stable and attractive dividend payouts are generally viewed more favorably by investors, which boosts market capitalization. The results suggest that while expanding market share contributes positively to firm value, excessive debt can undermine this advantage. Additionally, maintaining a consistent and attractive dividend policy can further enhance firm value by signaling financial health and stability to investors. This study provides critical insights for technology sector managers and investors, emphasizing the importance of balancing financial strategies, market positioning, and dividend distribution to maximize firm value.